Nanoencapsulation modulates aspartame metabolite exposure: Toxicokinetic, mechanistic, and pharmacological evaluation in a glucocorticoid dysfunction model - Sherine F. Fawzy; Al-Sayeda A. Newairy; Doaa A. Ghareeb; Shaymaa A. Abdulmalek; Hend M. Hussien; Maram Allam; Saber M. Eweda; Samar R. Saleh; Karim Raafat (Toxicology and Applied Pharmacology, 2026)

Retraction Note: Neuroprotective effect of ipriflavone against scopolamine-induced memory impairment in rats - Hani S. Hafez; Doaa A. Ghareeb; Samar R. Saleh; Mariam M. Abady; Maha A. El Demellawy; Hend Hussien; Nihad Abdel-Monem (Psychopharmacology, 2026)

Evaluation and selection of ground motion prediction equations for seismic hazard analysis in Northern Egypt - Samar Ghareeb; Rami Ibrahim; Toshiaki Yokoi; Mahmoud El-Hadidy; Mohsen M. Attia; Amr El-Sharkawy; Abdelbaset M. Abudeif (Journal of African Earth Sciences, 2026)

Combating Lead/HFD Neurotoxicity in Rats: The Synergistic Effect of 10-Hydroxydecanoic Acid and Zinc Oxide Nanoparticles - Samar R. Saleh; Esraa Atef; Adham M. Maher; Doaa A. Ghareeb; Eman Sheta; Saber M. Eweda (Biological Trace Element Research, 2025)

Attenuation of high-fat high-sucrose diet and CCl4-induced non-alcoholic steatohepatitis in rats by activating autophagy and SIGMAR1/GRP78/ITPR1 signaling using berberine-loaded albumin nanoparticles: in vivo prediction and in-silico molecular modeling - Samar R. Saleh; Fatema A. Younis; Sahar S. Abdelrahman; Azza A. Attia; Maha A. El‑Demellawy; Al‑Sayeda A. Newairy; Doaa A. Ghareeb (Journal of Pharmaceutical Investigation, 2025)
Purpose Non-alcoholic fatty liver disease is the most prevalent metabolic disorder that can lead to the development of non-alcoholic steatohepatitis (NASH) and, eventually, result in hepatocellular carcinoma. This study evaluated the therapeutic potential of berberine-loaded bovine serum albumin nanoparticles (BBR-BSA NPs) toward the induced NASH physical, biochemical, and ultrastructural changes. Methods NASH was induced in male rats by an high-fat high-sucrose diet (HFHSD) and repeated carbon tetrachloride (CCl 4 ) injections. The treated groups received HFHSD/CCl 4 and were then administered BBR, BBR-BSA NPs, BSA NPs, and Atorvastatin for four weeks. Finally, physical, liver function, lipid profile, hepatic oxidative stress, and inflammatory biomarkers were determined. Furthermore, hepatic sigma 1 receptor (SIGMAR1) and autophagy signaling proteins were evaluated. The hepatic transmission electron microscopic and histopathological examinations were also assessed. Finally, the chemical- and protein–protein interaction networks were presented using the visualization tools STITCH 5.0 and STRING databases. In addition, molecular docking analyses were conducted to illustrate the binding of BBR and Atorvastatin toward SREBP-2 and mTOR targets. Results The long-term administration of HFHSD/CCl 4 had the potential to develop a NASH model. This model is characterized by hepatic steatosis, necro-inflammation, and impaired endoplasmic reticulum-mitochondrial signaling. The results revealed an impaired SIGMAR1 and autophagy flux signaling pathways. In contrast, the administration of BBR-BSA NP improved the therapeutic properties of entrapped BBR on the alterations associated with NASH. The BBR-BSA NPs enhanced the autophagic flux and SIGMAR1 signaling modulators compared to BBR and Atorvastatin. The in-silico bioinformatics analysis demonstrated that BBR exhibited a more robust interaction with SREBP-2 and mTOR compared to Atorvastatin, which supports the in vivo results. Conclusion BBR-BSA NPs restored hepatic homeostasis and enhanced the free BBR’s hepatoprotection against the induced NASH via the upregulation of SIGMAR1 and autophagy flux signaling.

Correction: 10-Hydroxy Decanoic Acid and Zinc Oxide Nanoparticles Retrieve Nrf2/HO-1 and Caspase-3/Bax/Bcl-2 Signaling in Lead-Induced Testicular Toxicity - Adham M. Maher; Ghidaa A. Elsanosy; Doaa A. Ghareeb; Samar S. Elblehi; Samar R. Saleh (Biological Trace Element Research, 2024)

10-Hydroxy Decanoic Acid and Zinc Oxide Nanoparticles Retrieve Nrf2/HO-1 and Caspase-3/Bax/Bcl-2 Signaling in Lead-Induced Testicular Toxicity - Adham M. Maher; Ghidaa A. Elsanosy; Doaa A. Ghareeb; Samar S. Elblehi; Samar R. Saleh (Biological Trace Element Research, 2024)
There has been a significant increase in human exposure to heavy metals (HMs) over the course of the previous century, primarily due to the extensive industrial processes. Male infertility is a prominent complication associated with lead exposure, wherein lead has the potential to accumulate within the testes, resulting in oxidative stress and inflammation. In addition, 10-hydroxydecanoic acid (10-HDA) is a component found in the secretions of worker bees and possesses the capacity to mitigate oxidative stress and prevent inflammation. Due to their advantageous properties, zinc oxide nanoparticles (ZnO-NPs) possess a wide range of applications in the field of biomedicine. This study aimed to assess the therapeutic effect of 10-HDA and ZnO-NPs on testicular toxicity in rats induced by lead acetate (PbAc). PbAc was administered orally for a period of 3 months. Following that, 10-HDA and/or ZnO-NPs were administrated for 1 month. PbAc deformed seminal analysis, decreased seminal fructose and sex hormonal levels, and resulted in the development of histopathological complications. Additionally, PbAc increased MDA and decreased Nrf2 and HO-1 expression, confirmed by the declined antioxidant defense system. Furthermore, an increase in testicular inflammatory markers and the Bax/Bcl-2 ratio was observed subsequent to the administration of PbAc. The administration of 10-HDA and ZnO-NPs demonstrated significant efficacy in the restoration of semen quality, pituitary/gonadal hormones, antioxidants, and testicular histoarchitecture. Moreover, 10-HDA and ZnO-NPs decreased testicular inflammatory markers and apoptotic proteins (caspase-3 and Bax expression levels). In conclusion, combining 10-HDA and ZnO-NPs demonstrated synergistic potential in treating PbAc-induced testicular toxicity, thereby presenting a promising approach in nanomedicine and natural drugs.

Exploring the dynamics of bioactive metabolites changes in barley grains (Hordeum vulgare L.) during roasting: Insights from UPLC-QqQ-MS/MS analysis combined to chemometrics - Eman Shawky; Samar M. Bassam; Hanan S. Marzouk; Doaa A. Ghareeb; Samah M. El Sohafy (Food Research International, 2024)

Endorsement and phylogenetic analysis of some Fabaceae plants based on DNA barcoding - Nader R. Abdelsalam; Mohamed E. Hasan; Talha Javed; Samar M. A. Rabie; Houssam El-Din M. F. El-Wakeel; Amera F. Zaitoun; Aly Z. Abdelsalam; Hesham M. Aly; Rehab Y. Ghareeb; Alaa A. Hemeida; Adnan Noor Shah (Molecular Biology Reports, 2022)
Background DNA barcoding have been considered as a tool to facilitate species identification based on its simplicity and high-level accuracy in compression to the complexity and subjective biases linked to morphological identification of taxa. MaturaseK gene ( MatK gene) of the chloroplast is very vital in the plant system which is involved in the group II intron splicing. The main objective of this study is to determine the relative utility of the “ MatK ” chloroplast gene for barcoding in 15 legume as a tool to facilitate species identification based on their simplicity and high-level accuracy linked to morphological identification of taxa. Methods and Results MatK gene sequences were submitted to GenBank and the accession numbers were obtained with sequence length ranging from 730 to 1545 nucleotides. These DNA sequences were aligned with database sequence using PROMALS server , Clustal Omega server and Bioedit program. Maximum likelihood and neighbor-joining algorithms were employed for constructing phylogeny. Overall, these results indicated that the phylogenetic tree analysis and the evolutionary distances of an individual dataset of each species were agreed with a phylogenetic tree of all each other consisting of two clades, the first clade comprising (Enterolobium contortisiliquum, Albizia lebbek), Acacia saligna , Leucaena leucocephala, Dichrostachys Cinerea, (Delonix regia, Parkinsonia aculeata), (Senna surattensis, Cassia fistula, Cassia javanica) and Schotia brachypetala were more closely to each other, respectively. The remaining four species of Erythrina humeana, (Sophora secundiflora, Dalbergia Sissoo, Tipuana Tipu) constituted the second clade. Conclusion Moreover, their sequences could be successfully utilized in single nucleotide polymorphism or as part of the sequence as DNA fragment analysis utilizing polymerase chain reaction in plant systematic. Therefore, MatK gene is considered promising a candidate for DNA barcoding in the plant family Fabaceae and provides a clear relationship between the families.

Pharmacological implications of ipriflavone against environmental metal–induced neurodegeneration and dementia in rats - Hend M. Hussien; Doaa A. Ghareeb; Hany E. A. Ahmed; Hani S. Hafez; Samar R. Saleh (Environmental Science and Pollution Research, 2021)

Nanoparticles of ZnO/Berberine complex contract COVID-19 and respiratory co-bacterial infection in addition to elimination of hydroxychloroquine toxicity - Doaa A. Ghareeb; Samar R. Saleh; Mohamed G. Seadawy; Mohammed S. Nofal; Shaymaa A. Abdulmalek; Salma F. Hassan; Shaimaa M. Khedr; Miral G. AbdElwahab; Ahmed A. Sobhy; Ali saber Ali Abdel-Hamid; Abdelrahman Mohamed Yassin; Alshimaa A. Abd Elmoneam; et al. (Journal of Pharmaceutical Investigation, 2021)

Potential therapeutic and pharmacological strategies for SARS-CoV2 - Doaa A. Ghareeb; Samar R. Saleh; Mohammed S. Nofal; Mohamed M. Y. Kaddah; Salma. F. Hassan; Inas K. Seif; Sally A. El-Zahaby; Shaimaa M. Khedr; Marwa Y. Kenawy; Aliaa A. Masoud; Salma A. Soudi; Ahmed A. Sobhy; et al. (Journal of Pharmaceutical Investigation, 2021)

RETRACTED ARTICLE: Neuroprotective effect of ipriflavone against scopolamine-induced memory impairment in rats - Hani S. Hafez; Doaa A. Ghareeb; Samar R. Saleh; Mariam M. Abady; Maha A. El Demellawy; Hend Hussien; Nihad Abdel-Monem (Psychopharmacology, 2017)